(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Irrigation erosion is a process that has a major negative impact on agricultural production, which greatly reduces soil fertility and crop yields. Costs related to crop production will increase. Today in the country, more than 720 thousand hectares of irrigated areas are subject to irrigation erosion. According to the results of scientific research, in typical wetlands with slopes of more than 0.30, during the season, 24.6 tons of soil particles were washed away from each hectare of land under normal irrigation of soil particles by 6-12% when irrigated using transverse furrow furrows. Reduction of soil moisture depth to 0.8 m during irrigation will save 10-15%.